DC League of Super-Pets : the deluxe junior novelization - Lewman, David (Random House, 2022)
Krypto the Super-Dog and Superman are inseperable best friends, sharing the same superpowers and fighting crime in Metropolis side by side. When Superman and the rest of the Justice League are kidnapped, Krypto must convince a ragtag shelter pack-- Ace the hound, PB the potbellied pig, Merton the turtle, and Chip the squirrel-- to master their newfound powers and help him rescue the Super Heroes.